2018
DOI: 10.1017/s0033291718001617
|View full text |Cite
|
Sign up to set email alerts
|

Age and sex differences in hearing loss association with depressive symptoms: analyses of NHANES 2011–2012

Abstract: Moderate/worse speech frequency and HFHL are associated with depression in women ages 52-69 years, independent of other risk factors. Hearing screenings are likely to reduce delays in diagnosis and provide early opportunities for noise prevention counseling and access to hearing aids. Health professionals should be aware of depressive signs and symptoms in patients with hearing loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 37 publications
2
37
1
Order By: Relevance
“…In a community sample of 5832 subjects from Korea, self‐reported hearing loss was associated with significantly higher prevalence of depression and this association was magnified among those with dual hearing and visual impairment [65]. The United States National Health And Nutrition Examination Survey (NHANES) survey data showed that hearing loss was associated with increased frequency of depression using the PHQ‐9 measurement [66]. Another investigation based on clinical interviews with parents in Austria showed that the point and lifetime prevalence of depression were higher in a representative sample of deaf schoolchildren than in children without hearing loss [34].…”
Section: Discussionmentioning
confidence: 99%
“…In a community sample of 5832 subjects from Korea, self‐reported hearing loss was associated with significantly higher prevalence of depression and this association was magnified among those with dual hearing and visual impairment [65]. The United States National Health And Nutrition Examination Survey (NHANES) survey data showed that hearing loss was associated with increased frequency of depression using the PHQ‐9 measurement [66]. Another investigation based on clinical interviews with parents in Austria showed that the point and lifetime prevalence of depression were higher in a representative sample of deaf schoolchildren than in children without hearing loss [34].…”
Section: Discussionmentioning
confidence: 99%
“…In patients, it has been shown that auditory cortex activation and auditory perception and processing are impaired in depression (Zwanzger et al, 2012; Bonetti et al, 2017; Zweerings et al, 2019). Moreover, age-related hearing loss has been associated with late life depression (Husain et al, 2014; Rutherford et al, 2018; Scinicariello et al, 2019), and in animals, chronic restraint stress decreased glucose metabolism in the auditory cortex (Wei et al, 2018). It would be relevant to know whether antidepressant medication reverts auditory dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…At year 5, individuals with increased depressive symptoms had greater hearing loss measured by audiometric threshold for low-frequency and mid-frequency sounds compared with those with lower levels of depressive symptoms. In a study of NHANES data, both speech-frequency hearing loss and high-frequency hearing loss were associated with increased frequency of depression using the PHQ-9 (Scinicariello et al ., 2018).…”
Section: Hearing Loss and Psychiatric Disordersmentioning
confidence: 99%